FRI0205 Comparison of work disability, depression and quality of life in patients with ankylosing spondylitis vs. psoriatic arthritis: interim results from the complete study. (12th June 2018) - Khraishi, M.; Bessette, L.; Haraoui, B.; Florica, B.; Setty, Y.; Teo, M.; Remple, V.
Abstract : Background: Ankylosing Spondylitis (AS) and Psoriatic arthritis (PsA) are chronic progressive inflammatory diseases associated with severe pain and joint damage which may negatively impact patient reported outcomes (PRO), such as ability to work, depression and quality of life (QoL). Objectives: To assess differences in PROs between patients with active AS and PsA requiring change in their treating regimen. Methods: Patients eligible for the COMPLETE studies are anti-TNFα naïve adults, with active AS or PsA who require change in their regimen per the treating physician. Here, baseline data from patients enrolled between Jul/2011-Jun/2017 were included. PROs included the WLQ, BDI, and SF-12. Disease activity was classified as active/severe vs low/moderate based on BASDAI (≥4 vs<4) for AS and based on DAS28 (≥5.1 vs<5.1) for PsA. PsA patients were further stratified as per BSA ≥3% vs<3%. Differences between AS and PsA in WLQ, SF-12, and BDI were assessed with multivariate generalised linear models. Results: 528 AS and 317 PsA (41% with BSA ≥3%) patients were included. Upon multivariate adjustment, AS patients showed a trend towards higher scores in the SF-12 Physical Functioning subdomain compared to PsA patients with BSA <3% (p=0.069) at baseline (table 1). Furthermore, PsA patients with BSA ≥3% had significantly higher scores in the SF-12 Role Functioning (Physical) subdomain (p=0.031) and showed a trend towards higher scores in the SF-12 Mental Health subdomain (p=0.085) compared to those with BSA <3%. No differences were observed between groups in any of the remaining SF-12 subdomains, WLQ, or BDI. In terms of other determinants of PROs, high/very high disease state was associated with significantly higher BDI and worse scores in all WLQ and SF-12 dimensions and female gender was found to be a significant predictor of higher BDI scores and lower scores in the SF-12 physical functioning, vitality, social functioning and mental health subdomains. Conclusions: AS and PsA affect multiple aspects of patients' lives without significant differences between the two diseases. Higher disease severity is associated with depressive symptoms and greater impairment in daily activities and work productivity. The impact of disease activity and treatment response over time on PRO will be evaluated in future analyses. Reference: [1] JSS Medical Research, Montreal, Canada. Disclosure of Interest: M. Khraishi Consultant for: AbbVie, Speakers bureau: AbbVie, L. Bessette Consultant for: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Celgene, Lilly, Novartis, Speakers bureau: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Lilly, Novartis, B. Haraoui Grant/research support from: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, and UCB, Speakers bureau: Amgen, BMS, Janssen, Pfizer, and UCB, B. Florica: None declared, Y. Setty Consultant for: AbbVie, M. Teo Consultant for: AbbVie, Amgen, Celgene, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi-Genzyme, Speakers bureau: AbbVie, Roche, V. Remple Shareholder of: AbbVie, Employee of: AbbVie